ANALYZE THE ESSENCE OF CULTURAL ATTRACTIONS SYMBOLS OF THE THAI NATION - Phrabaidika Uthai Suciṇṇo (Pitakhongsakul) (Journal of Contemporary Buddhist Society = JCBS, 2024)
Analyze the essence of this symbolic cultural attraction of the Thai nation. There are two objectives: 1) to study the symbolic cultural tourism of the Thai nation; 2) to analyze the essence of the symbolic cultural tourism of the nation. by studying from relevant documents and research The study found that Cultural tourism in Thailand refers to a tourism process that emphasizes the cultural uniqueness of Thailand. Tourists experience and learn about the cultural heritage. history. arts. and traditions of the destination. Cultural tourism promotes environmental conservation and the preservation of local cultural identity while generating sustainable income for local communities. Thailand has a distinctive culture that stands out in approximately five aspects. These include: 1) Buddhist culture with beautiful temples (Wat) scattered throughout the country. and various Buddhist customs and traditions observed throughout the year. 2) Songkran festival. known worldwide for its water splashing tradition. 3) Thai manners. a unique identity loved by tourists. encompassing smiles and the wai gesture. 4) Traditional Thai attire. appreciated by foreigners who enjoy wearing it. 5) Thai cuisine. an essential part of the experience. especially dishes like Tom Yum Goong. which has become a national symbol recognized globally.